HOW STUDENTS WORK WITH PISA-LIKE MATHEMATICAL TASKS USING COVID-19 CONTEXT - Zulkardi Zulkardi; Meryansumayeka Meryansumayeka; Ratu Ilma Indra Putri; Zahra Alwi; Duano Sapta Nusantara; Sahala Martua Ambarita; Yulianita Maharani; Linda Puspitasari (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
School students can use a sequence of contextual tasks to learn mathematics. We can use Covid-19 as a phenomenon or context to exploit in learning mathematics. This article describes how students learn with mathematical problems that adapted PISA tasks and used the Covid-19 context. This study involved 29 secondary-level students, 15 years old, and each has different levels of mathematical skills. We use three phases of design research as the research method. Data were collected using observation, interviews, and documents. Then, they were analyzed descriptively. The result showed there were ten problems developed, and students were asked to work with those problems. We found that there are steps in how students understand and solve the problem. First, if students find a picture in the task, then they observe at the picture, read the question, and then start working to solve the problem. Second, if students find a table with less data, students refer to all data in solving the problem. Third if students find a table which has a lot of data, then some students calculate all of the data and other only compared among them. We’d like to encourage students to understand the problem before solving the problem. They do this by observing the pictures, comprehending the tables and also the questions.